Anomalous Ohmic Loss in Solid Oxide Fuel Cells with Doped Ceria Interlayers. (2nd June 2015) - Zhou, Xiao-Dong; Lu, Z; Templeton, J; Stevenson, J W
Abstract : The ohmic resistances were characterized in anode-supported and electrolyte-supported single cells by using electrochemical impedance spectroscopy from 500 to 850 °C. Ceria layers with various porosities were employed, which were found to play a governing role on the accelerated ohmic resistance reported in literature. The ohmic resistance with a porous doped ceria barrier layer was as large as three times of that contributed by YSZ. Further research was carried out by using a variety of YSZ electrolyte thicknesses, which were fabricated by tape casting and lamination. A linear relationship was found between the ohmic resistance of the fuel cell and the YSZ electrolyte thickness. Calculations of the contribution of the YSZ electrolyte to the total ohmic resistance show that (1) YSZ is still a satisfactory electrolyte at temperatures above 600 °C, (2) if there is no doped ceira layer, the total ohmic loss is governed by YSZ while the interfacial resistance is negligible, and (3) explorations should be directed to reduce the interception resistance to achieve significant improvement in cell performance with a doped ceria interlayer.